LABOR IN FOREIGN COMPANIES ASSOCIATED WITH THE PRINCIPLES OF NATIONAL TREATMENT IN GATS / WTO FRAMEWORK - Desty Anggie Mustika; Amiludin Amiludin (Jurnal Hukum Replik, 2020)
Since The Issuance Of Law No. 1 Of 1967 Concerning Planting Foreign Capital And Is Now Replaced By-Law No. 25 Years 2007 Regarding Investment There Are No More Foreign Companies Nationalized By The Government And There Is A Political Promise Of The President Who Guarantee There Will Be No Nationalization Of Foreign Companies In Indonesian Regional Foreign Investment Forum. Although There Is Protection Nationalization Of Foreign Companies There Are Various Government Policies For The National Interest, One Of Which Is By Requiring Foreign Companies To Use Local Labor Which Can Be Called The Indonesianization Of Labor In The Company Foreign Law Contained In Act Number 13 Of 2003 Concerning Employment Article 43 To 49. Indeed This Is Indonesia's Sovereignty To Protect Its Domestic Interests Especially The Rights Of Its Citizens To Get Jobs, But Within Indonesia's International Trade In Services Must Comply Various Agreed International Regulations Listed In The GATS / WTO, Whether Indonesianization Of Workers In Foreign Companies This Is Following The Principle Of National Treatment In GATS And Whether This Government Action Is Following The Provisions In The GATS / WTO. By Conducting Descriptive Analytical Research With Methods Normative Juridical Approach, The Author Will Examine Various Regulations National Legislation Related To The Use Of Labor In Foreign Companies And Compare Them Whether This Is Following Existing International Agreements, Especially Within The GATS / WTO. The Results Of This Study Indicate That The Indonesianization Of Workers In Foreign Companies Does Not Violate The Principle Of National Treatment GATS Due To Indonesianization Of Labor Also Applies In Companies Domestic. Indonesianization Are Energy Absorption Processes Local Work In A Foreign Company As A Way Of Dealing With It Globalization Of Trade In Services Contained As One Type Services That Have Been Regulated In GATS Are Commercial Presence.Keywords: Indonesianization of Labor, National Treatment, GATS / WTO